The Political Legal Implications Of The Liberalization Of Foreign Labor Use in National Strategic Projects From The Perspective Of The Job Creation Law - Maina Listuti, Eka; Eka Putri, Rima; Syahuri, Taufiqurrohman (Universitas Ekasakti, 2023)
Legal politics have a significant impact in the era of globalization and economic growth, especially in the context of the use of Foreign Labor in Indonesia's national strategic projects. While the liberalization of foreign labor is intended to support foreign investment and infrastructure development, it has also raised issues regarding the legal politics related to the liberalization of foreign labor use in national strategic projects from the perspective of the Job Creation Law, and how these legal politics impact local employment. The research methodology employed in this study is juridical normative, using legal regulations as the basis for analyzing these issues. The research results indicate that the legal politics in the form of policy that has led to the liberalization of foreign labor use has created inequality in employment opportunities between Foreign Labor and local workers, making it difficult for local workers to find suitable employment. This is due to the government being the employer of Foreign Labor, with the authority to regulate their use in national strategic projects. The implications of liberalizing the use of Foreign Labor have had an impact on employment opportunities and the welfare of local workers, which has led to an unbalanced situation in national strategic projects. The dependence on Foreign Labor increases project costs, while trained local workers can reduce them.